Targeting KRAS in Non-Small Cell Lung Cancer - Corral de la Fuente, Elena; Olmedo Garcia, Maria Eugenia; Gomez Rueda, Ana; Lage, Yolanda; Garrido, Pilar (Frontiers in Oncology, 2022)
Kirsten Rat Sarcoma viral oncogene homolog (KRAS) is the most frequently altered oncogene in Non-Small Cell Lung Cancer (NSCLC). KRAS mutant tumors constitute a heterogeneous group of diseases, different from other oncogene-derived tumors in terms of biology and response to treatment, which hinders the development of effective drugs against KRAS. Therefore, for decades, despite enormous efforts invested in the development of drugs aimed at inhibiting KRAS or its signaling pathways, KRAS was considered to be undruggable. Recently, the discovery of a new pocket under the effector binding switch II region of KRAS G12C has allowed the development of direct KRAS inhibitors such as sotorasib, the first FDA-approved drug targeting KRAS G12C, or adagrasib, initiating a new exciting era. However, treatment with targeted KRAS G12C inhibitors also leads to resistance, and understanding the possible mechanisms of resistance and which drugs could be useful to overcome it is key. Among others, KRAS G12C (ON) tricomplex inhibitors and different combination therapy strategies are being analyzed in clinical trials. Another area of interest is the potential role of co-mutations in treatment selection, particularly immunotherapy. The best first-line strategy remains to be determined and, due to the heterogeneity of KRAS, is likely to be based on combination therapies.